PERSEPSI KEMANFAATAN DAN PERSEPSI KEMUDAHAN DENGAN MINAT PENGGUNAAN SEBAGAI VARIABEL INTERVENING TERHADAP PERILAKU PENGGUNAAN SISTEM - Prabawalingga, I Gst. Ngr Mayun; Yadnyana, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.10.TAHUN 2016, 2016)
This study aims to determine the effect of the perception of usefulness and perceived ease with interest in the use as an intervening variable and its influence on the behavior of the system using Electronic Data Capture (EDC). The population in this study is the overall merchant using EDC systems PT. Indonesia Union Pay (Indopay) in Denpasar. Sampling was done by purposive sampling, with criteria merchants using EDC system Indopay in Denpasar. The samples used in this study is as much as 192 merchants. Technical analysis of the data used is Structural Equation Modeling (SEM). The results of this study show that: 1) Perception of expediency positive effect on the behavior of use, 2) Perceived ease positive effect on the behavior of use, 3) Perceived usefulness positively affects the desirability of using, 4) Perceived ease positive influence on interest in the use, 5) Interests of use positive effect on the behavior of use, 6) Perceived usefulness positively affects the usage behavior through the use of interest, 7) Perceived ease of use positively affects behavior through the use of interest.
Keywords: Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), Perceived Benefits, Perceived Ease, Interests of Use, Behavior of Use